Комплекс украшений из разрушенного женского погребения около церкви Иоанна Предтечи в Керчи - Макарова, Т.И. (Материалы по археологии, истории и этнографии Таврии, 2005)
8 октября 1963 г. в Керчи при земляных работах на территории бывшего старого рынка (ныне - площадь Толстого), в 40 м к северо-востоку от церкви Иоанна Предтечи было обнаружено женское погребение с богатым инвентарем, включающим более ста предметов. Случайность находки не способствовала сохранению сведений о характере самого погребения, но вещи в количестве 103 предметов все же попали в Керченский музей (инв. № К-9938,1-29). Они представляют собой интересный богатый комплекс женских украшений. The burial destroyed during the excavation works in Kerch on the former Market Square in 1963 is interesting in an unusual for medieval antiquities of the Crimea richness of the inventory. The analogies in the cemetery at John the Baptist Church enable us to date this burial back to the 11th - 12th cent. It does not contradict to earlier dating of stone beads that had always been in use for a long period. Unique preservation of glass painted bracelets enriches our overview about Byzantines glass making. Gold and silver jewellery - rings and original pendant - demonstrate favourite techniques of Byzantine jewellery: filigree, gilding silver, using silver appliqué work on lead that was used in the town jewellery work in Byzantium. The find of the burial dating back to the 11 th -12th century at the distance of 40 meters from the walls of John the Baptist Church testifies to the fact that church cemetery was growing rapidly. It also testifies to the fact that the population of the city at the period when it was called Korchev was also growing.